2020
DOI: 10.3390/ani10091468
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolyzed Yeast Supplementation in Calf Starter Promotes Innate Immune Responses in Holstein Calves under Weaning Stress Condition

Abstract: Weaned calves are susceptible to infectious diseases because of the stress and malnutrition that occurs during weaning. Therefore, the dairy industry requires effective feed additives to ameliorate stress responses and promote immunity. This study aimed to investigate the effects of hydrolyzed yeast (HY) supplementation on the growth performance, immune and stress parameters, and health status of calves after weaning. Eighteen Holstein calves were randomly assigned to two groups, either receiving a control cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 56 publications
0
6
0
1
Order By: Relevance
“…Previous research confirmed that weaning reduced immunity function, making invasion by external pathogenic microorganisms easier [27]. Immunoglobulin and cytokines are an important part of the immune system [28].…”
Section: Serum Immunitymentioning
confidence: 95%
“…Previous research confirmed that weaning reduced immunity function, making invasion by external pathogenic microorganisms easier [27]. Immunoglobulin and cytokines are an important part of the immune system [28].…”
Section: Serum Immunitymentioning
confidence: 95%
“…Neutrophils can protect livestock against the most common infectious diseases [ 56 ]. Kim et al [ 57 ] observed that Holstein calves fed HY showed enhanced neutrophils. Similarly, Wang et al [ 14 ] indicated that live yeast increases the expression of genes that improve the function of neutrophils, especially those that code for the IL-4 receptor and IL-1B in dairy cattle.…”
Section: Discussionmentioning
confidence: 99%
“…Los casos de diarrea fueron registrados cuando las terneras defecaron desde heces blandas hasta fluidas, con aumento de la frecuencia y pérdida del control fisiológico de la evacuación de las heces; así como la presentación de deshidratación, pérdida de peso, quejidos, dolor abdominal, decúbito o muerte. Mientras tanto, los eventos asociados con enfermedad respiratoria fueron registrados cuando la ternera mostró secreción patológica de las fosas nasales, tos, apatía, disnea, fiebre, decúbito o muerte (Karle et al, 2019;Kim et al, 2020;Timmerman et al, 2005). Además, la respuesta humoral frente a la inmunización en terneras contra el VDVB fue determinada mediante la prueba de virus neutralización (PVN).…”
Section: Estatus De Saludunclassified